The ethical climate relationships with organizational supports in oorganizational behaviors of nurses in public hospitals in Rasht province - Iraj shakerinia (Tehran University of Medical Sciences, 2012)
Background: The organizational Citizenship behaviors in an appropriate and desirable in performing the duties among nurses is a valuable point. Most of nurses usually meet organizational citizenship behaviors which are enable them to attract other staffs and patients. It might be continues in job all togethersto treatment process with more productivity. Materials and methods: A descriptive study approach consisted of 130 female nurses who worked in the emergency, surgery, women, children and the heart wards in the Rasht public hospital were asked by standard questionaire throughtout the moral atmosphere of that hospital with institutional support, and behaviors in a civic organization to complete a demographic questionnaire. Data obtained with the correlation test, Regression analysis and ONE-way analysis of Variance were analyzed. Results: There are significant relationships between moral climate, organizational supports and organizational civil behavior among nurses in the Rasht hohospital (p<0/01). Regression analysis showed that the correlation between hospital ethics climates and organizational supports. Changing the moral climates of the hospital has been able to predicted variance related to the organization of civil behavior among nurses (p<0/01). Organizational supports failed to predict of civil behavior among nurses. Conclusion: Results showed that the moral climate affected in the organization citizenship behavior of nurses. It means that organizational citizenship behavior plays an important role to efficient conducting of the professional activities among nurses. Health care organizations could provide an appropriate training to enhance the ethical climate in their organizations to help ultimate nursing services in achieving to appropriate culture.